Advertisement Remove all ads

Solve the Following Equation: (2x+3)(3x-7)=0 - Mathematics

Sum

Solve the following equation:

(2x+3) (3x-7) = 0

Advertisement Remove all ads

Solution

(2x + 3)(3x - 7) = 0

⇒ (2x + 3) = (3x - 7) = o 

⇒ 2x = - 3, 3x = 7 

⇒ x = `-3/2` , x = `7/3`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Frank ICSE Class 10 Mathematics Part 2
Chapter 6 Quadratic Equations
Exercise 6.1 | Q 2
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×